Analisis Perubahan Resistivitas Batuan Akibat Pencemaran Limbah Cair Menggunakan Pendekatan Laboratorium - Helmi Alfiaturrohmah; Rohmi Khoriun Nisa; Donny Harya Juanda; Firdha Kusuma Ayu Anggraeni; Novita Risna Sari (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2023)
Indonesia faces very complex problems in the management of groundwater resources. Industrial wastewater that is not managed properly and discharged into the environment will also have a negative impact on the surrounding community. The Wenner Schlumberger geoelectric method is one of the geophysical methods used to determine soil properties, especially oil content. The geoelectric method is one of the geophysical methods to determine changes in the specific resistance of rock layers below the ground surface. The research will be conducted using 2 methods, namely a direct approach with simulation experiments in the laboratory and a literature approach with literature. The results of the data obtained from the measurement of oil liquid waste injected into the rock arrangement cause the rock resistivity to have a high value due to the low electrical conductivity of the oil. This is because oil is a material that has good insulator properties.